2015
DOI: 10.1310/hpj5010-900
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Safety of a Vancomycin Nomogram Used to Achieve Target Trough Concentrations

Abstract: Background: Dosing vancomycin to achieve target concentrations of 15 to 20 mg/L has been recommended for select infections. To date, few vancomycin nomograms designed to target these higher concentrations have been published, and only one has been published in North America. Based on the success of this nomogram in developing empiric vancomycin regimens that achieve higher target trough concentrations with low rates of nephrotoxicity, a vancomycin nomogram targeting concentrations of 15 to 20 mg/L was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Five of the six studies were from the US 35 , 36 , 38 40 and one from Australia. 37 Three studies reported the population as number of patients, with 263 in the intervention group and 274 receiving usual care, 35 37 and one study reported treatment courses, with 200 in the intervention group and 279 receiving usual care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of the six studies were from the US 35 , 36 , 38 40 and one from Australia. 37 Three studies reported the population as number of patients, with 263 in the intervention group and 274 receiving usual care, 35 37 and one study reported treatment courses, with 200 in the intervention group and 279 receiving usual care.…”
Section: Resultsmentioning
confidence: 99%
“… 37 , 38 Two studies employed guidance and education meetings, 36 one utilized education meetings and dissemination of educational material, 40 and another used educational meetings only. 39 Of the four studies using guidance, two employed a clinical practice guideline, 37 , 38 one a nomogram, 36 and one an undefined policy change. 35 Dissemination of educational materials was employed in three studies using a pocket reference card ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%